2015
DOI: 10.1007/s13361-015-1305-9
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility Spectrometry-Hydrogen Deuterium Exchange Mass Spectrometry of Anions: Part 3. Estimating Surface Area Exposure by Deuterium Uptake

Abstract: Gas-phase Hydrogen deuterium exchange (HDX), collision cross section (CCS) measurement, and molecular dynamics simulation (MDS) techniques were utilized to develop and compare three methods for estimating the relative surface area exposure of separate peptide chains within bovine insulin ions. Electrosprayed [M−3H]3− and [M−5H]5− insulin ions produced a single conformer type with respective collision cross sections of 528 ± 5 Å2 and 808 ± 2 Å2. [M−4H]4− ions were comprised of more compact (Ω = 676 ± 3 Å2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Previous experiments have shown that per-residue HDX values can provide information about the relative distances of heteroatom sites to charge sites and deuterium incorporation sites, the surface accessibility of residues, and the charge site configuration of the peptide ions [8, 20, 25, 26]. In this manuscript, HAS scoring coupled with a NEC model is implemented for each candidate structure to produce its theoretical per-residue uptake pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have shown that per-residue HDX values can provide information about the relative distances of heteroatom sites to charge sites and deuterium incorporation sites, the surface accessibility of residues, and the charge site configuration of the peptide ions [8, 20, 25, 26]. In this manuscript, HAS scoring coupled with a NEC model is implemented for each candidate structure to produce its theoretical per-residue uptake pattern.…”
Section: Resultsmentioning
confidence: 99%
“…To address this problem, in separate studies, the contribution of each residue to the HDX rate for select conformer types was measured; using the same distance model, theoretical contributions to rate better approximated measured contributions for in - silico structures intended to represent conformer type [20]. Because measuring the contributions to rate constants at the individual amino acid residue level is an extremely time-intensive process and difficult to obtain for larger ions, an effective collision model was proposed to describe deuterium uptake levels at different partial pressures of D 2 O [25, 26] for select ion conformers.…”
Section: Introductionmentioning
confidence: 99%
“…To begin addressing these issues, gas-phase HDX has been introduced as a second criterion for structural characterization [27-29, 61, 62]. In the second installment of this work, comparisons of the experimental deuterium uptake values and the hypothetical values (obtained from a modified algorithm assessing the accessibility of hydrogens on candidate structures) are used to improve conformer selection and to assign relative population values along a MD trajectory.…”
Section: Resultsmentioning
confidence: 99%
“…35,37,43,44 Therefore, HDX rates implicitly involve structural changes and dynamics in proteins. 29 A variety of models have been used to determine protein conformational states using Monte Carlo (MC) 38,45 or molecular dynamics (MD) 2931,39,40,42,4654 approaches.…”
Section: Introductionmentioning
confidence: 99%